Regiospecific ortho‐C−H Allylation of Benzoic Acids. Issue 44 (5th March 2018) - Trita, A. Stefania; Biafora, Agostino; Pichette Drapeau, Martin; Weber, Philip; Gooßen, Lukas J.
Abstract: A carboxylate‐directed ortho ‐C−H functionalization has been developed and it allows the regiospecific introduction of allyl residues to benzoic acids. In the presence of a [Ru( p ‐cymene)Cl2 ]2 and K3 PO4, benzoic acids react with allyl acetates at only 50 °C to give the corresponding ortho ‐allylbenzoic acids. The protocol is generally applicable to both electron‐rich and electron‐poor benzoic acids in combination with linear and branched allyl acetates. The products can be further functionalized in situ, for example, by double‐bond migration, lactonization, or decarboxylation. Abstract : Direct play : A carboxylate‐directed ortho ‐allylation of benzoic acids is achieved in the presence of [Ru( p ‐cymene)Cl2 ]2 . The reaction is based on widely available, structurally diverse (hetero)aromatic carboxylate substrates and proceeds under remarkably mild reaction conditions. It is widely applicable to (hetero)aromatic benzoic acids and the products can be transformed in situ by acyloxylation, double‐bond isomerization, or protodecarboxylation.